2010
DOI: 10.1080/01634372.2010.515290
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions of Dementia Among Korean American Immigrants

Abstract: To better understand conceptualizations of dementia, this study explored causal attributions of dementia among 209 Korean Americans, using a self-administered questionnaire in Korean. Findings show that Korean Americans endorsed various causal attributions. Factor analysis yielded 3 dimensions of their attributions including psychological, physical/environmental, and cognitive/social. Bivariate analyses showed that younger age and higher education were related to more physical/environmental attributions, and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Eight studies indicated differences in perceptions by age group (Low and Anstey, 2007; Park et al , 2008; Low and Anstey, 2009; Lee et al , 2010; Anderson et al ., 2011; Bowes et al, 2012; McParland et al , 2012; Riva et al , 2012 ). Anderson et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies indicated differences in perceptions by age group (Low and Anstey, 2007; Park et al , 2008; Low and Anstey, 2009; Lee et al , 2010; Anderson et al ., 2011; Bowes et al, 2012; McParland et al , 2012; Riva et al , 2012 ). Anderson et al .…”
Section: Resultsmentioning
confidence: 99%
“…Perceptions about cognitive health and impairment among various racial/ethnic groups were examined in an additional five studies (Otilingam and Gatz, 2008; Lee et al , 2010, Stansbury et al , 2010a; 2010b; Rovner et al , 2013). In a survey study with 209 South Korean American adults aged 40 years or older, most participants reported that not keeping the mind active (80%), social and physical inactivity due to living alone or in isolation (75%), problems with brain chemistry (71%), stress (62%), introverted or passive personality (61%), or the South Korean concept of han (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Korean Americans often consider forgetfulness in old age as a sign of Alzheimer's disease (AD), but believe AD to be a normal part of aging; Korean Americans also lack knowledge about treatments, diagnoses, and causes of AD; and some believe lifetime stress factors and hardship can cause dementia (Jang, Kim, & Chiriboga, 2010;Lee, Diwan, & Yeo, 2010;. Another misconception about dementia shared by many Korean Americans is the belief that dementia is a form of insanity (Jang et al, 2010;, perhaps because dementia symptoms resemble symptoms of mental illness, such as delusion or agitation (Liu, Hinton, Tran, Hinton, & Baker, 2008).…”
Section: Family Caregiving Among Korean Americansmentioning
confidence: 99%
“…Pathological forgetfulness was viewed as a normal process of aging among different AA subgroups (i.e., Korean Americans, Vietnamese Americans, Chinese Americans, Filipino Americans, Vietnamese Americans, and Asian Indians) [10, 31, 43, 96-99, 102, 103, 105, 107-121, 123, 126-128, 130]. Additionally, Chinese Americans and Korean Americans (along with other minority groups such as African Americans and Latino Americans) attributed AD to psychosocial factors whereas Whites attributed AD to biomedical factors such as brain, body, disease, and genetics [8,125]. One important consideration was access to quality information on ADRD; one study evaluated the quality of dementia-related information that is available online (e.g., signs and symptoms) and determined that quality is lower in simplified Chinese compared to information in English [122].…”
Section: Knowledgementioning
confidence: 99%